On the Time Stability of the Output-Capital Ratio - Carlo D'Adda; Antonello Eugenio Scorcu (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2002)
This paper is concerned with the role of the output-capital ratio in growth models. In the first part we highlight the behaviour of the output-capital ratio along the balanced growth path in the models of Solow (1956) and Romer (1986). In the second part we assess the stability of the ratio for some industrial countries.
Keywords: 330